ANALISIS REPRESENTASI MATEMATIS PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL DI SMP NEGERI 1 SIGI DITINJAU DARI PERBEDAAN GENDER: Analysis of Mathematical Representation in a Linear Equation System with Two Variables Material at SMP Negeri 1 Sigi Reviewed from Gender Differences - Nugroho Alfarizi; Baharuddin Paloloang; Dasa Ismaimuza; Pathuddin Pathuddin (Jurnal Elektronik Pendidikan Matematika Tadulako, 2025)
This study aims to obtain a description of students' mathematical representation in solving problems of two-variable linear equation systems in grade IX students at SMP Negeri 1 Sigi based on gender differences. This type of research is descriptive research with a qualitative approach. The subjects in this study were 2 students, including male and female students with moderate mathematical abilities. The results of this study indicate that (1) In the visual representation indicator, male students can already represent problems in the form of tables, but have not been able to make solution graphs, while female students cannot represent the problems given in the form of pictures/graphs to solve problems. (2) In the verbal representation indicator, male students have errors in writing several words, while female students have deficiencies in making efficient sentences, but can explore the answers further during the interview. (3) In the symbol representation indicator, male students can represent the given problem into a mathematical expression to find the right solution, while female students cannot solve the problem completely.